1997
DOI: 10.1097/00004872-199715010-00006
|View full text |Cite
|
Sign up to set email alerts
|

An abnormal sodium metabolism in Japanese patients with essential hypertension, judged by serum sodium distribution, renal function and the renin-aldosterone system

Abstract: Serum sodium distribution patterns differed between normal subjects and patients with essential hypertension in this Japanese population. The deterioration of renal function and increased sodium intake did not explain this abnormal sodium metabolism. A higher serum sodium concentration is related to an elevated blood pressure, and, in some patients, an inappropriate elevation of plasma aldosterone levels. Of the Japanese hypertensive patients, 10-14% exhibited serum sodium concentrations of 147 mmol/l or more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2001
2001
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 31 publications
1
37
0
Order By: Relevance
“…The serum sodium distribution in the hypertensive patients was shifted by Ϸ2 mmol/L toward the higher values. 41 It is possible that some of these differences could be explained by undetected primary aldosteronism in some individuals, but this is unlikely to explain all of the differences. Furthermore, in the study by Bulpitt et al, 38 there was still a significant relationship between plasma sodium and systolic blood pressure after adjusting for potential confounding factors (eg, age, body mass index, serum potassium, calcium, proteins, blood hemoglobin, mean corpuscular volume, and alcohol intake).…”
Section: Discussionmentioning
confidence: 99%
“…The serum sodium distribution in the hypertensive patients was shifted by Ϸ2 mmol/L toward the higher values. 41 It is possible that some of these differences could be explained by undetected primary aldosteronism in some individuals, but this is unlikely to explain all of the differences. Furthermore, in the study by Bulpitt et al, 38 there was still a significant relationship between plasma sodium and systolic blood pressure after adjusting for potential confounding factors (eg, age, body mass index, serum potassium, calcium, proteins, blood hemoglobin, mean corpuscular volume, and alcohol intake).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, these findings had some parallels with regard to ARR when applied to the hypertensive population. Komiya et al 47 observed that ARR related positively to age and plasma sodium concentration in 741 patients with essential hypertension, relationships which were not detectable using plasma aldosterone levels. 48 A recent study reported by Schlaich et al 49 involving young adults with mild hypertension suggested that there was a linear relationship between poor plasma aldosterone suppression with deterioration of left ventricular diastolic function in response to salt loading.…”
Section: The Issue Is Whether Hyperaldosteronism Varies Inmentioning
confidence: 99%
“…39 The structural changes in intramyocardial coronary arteries induced by a high salt diet are accompanied by a number of metabolic alterations including an increased generation of reactive oxygen species 40 which, among other effects, oxidise nitric oxide thus reducing its dilator effect 41,42 and the arteriolar response to acetylcholine. 40 As a rise in salt intake is usually accompanied by a small rise in plasma sodium and plasma sodium tends to be raised in essential hypertension 43 it is possible that the effect of a small change in sodium concentration on in vitro cultures of endothelial cells may also be relevant to a consideration of the effect of dietary salt on vessels in vivo. For instance increasing the sodium concentration of the culture fluid of cultured myocardial myocytes and vascular smooth muscle by 6 mM/l for 5 days causes hypertrophy.…”
Section: Vesselsmentioning
confidence: 99%